Investigation on the Effects of Hydroponic-planting Versus Soil-planting Using Plectranthus amboinicus as a Plant Model - Shaila Mohana Dass; Tsun-Thai Chai; Fai-Chu Wong (Journal of Tropical Life Science, 2022)
Hydroponic system is a method of growing crops or plants in a soilless system, by suspending the plant crops in a nutrient-rich solution, with reduced interferences from such factors as soil quality, irrigation and climate. However, there is limited information available on how hydroponic planting will affect the plant’s bioactivities, as well as the associated biochemical, mineral, phytochemical and antioxidant enzyme contents. In this study, we used Plectranthus amboinicus (Indian borage) as a medicinal plant model, to investigate the differences between hydroponic-planted (HP) versus soil-planted (SP) plants. Here, aqueous extracts of Indian borage from HP and SP samples were prepared, followed by testing for their phytochemical, mineral, chlorophyll and carotenoid contents. Based on our results, SP sample was detected with higher antioxidant potentials, using two different radical scavenging assays. This observation is correlating to the higher phytochemical contents (total phenolic, flavonoid, and hydroxycinnamic acids contents), as well as higher chlorophyll and carotenoid contents, detected in the SP sample. However, no significant difference was detected between HP and SP samples, in terms of their protein protection potentials. On the other hand, HP sample was tested with higher mineral contents (iron, copper, magnesium and calcium) using the atomic absorption spectroscopy method. Additionally, higher antioxidative enzymes (superoxide dismutase, catalase) were also detected in the HP sample using biochemical assays. In the future study, more plant models can be included in the comparison between HP and SP effects, to determine if a similar phenomenon is observed. Through similar studies, it is hoped that more related information could be gathered and help to guide the choice of suitable planting systems with regard to food security, in terms of both harvest yields and nutritional contents.